Compliance by Design Registration-to-Filing Pathways and Friction Points. - Chelsea Olivia; Refka Selegi Fadila; Wakhidatur Rizqi Zulfarida; Devita Vidya Anggraini; Clodiya Ikhtiarsyah; Falisya Cyntia Putri; Refansyah Ataullah (Journal of Strategic Behaviour Accounting, 2026)
The purpose of this research is to identify potential problem areas that taxpayers many encounter in, the registration and filing and payment processes, and to propose a compliance by design strategy as most suitable for improving the type of compliance outcomes. This research is motivated by low compliance conversion rates due to administrative frictions like systen errors, delayed identity authentication, document complekity and weak integration between e-billing systens and e-filing platforms. The study employs the process audit technique to map the compliance pathway. The data collection includes the regulatory review documents, live observation and screen capture of the online systems of the Directorate General of Taxes and a comparative in Indonesia, Japan and Taiwan. The research instrument used include a service blueprint, system activity logs and a friction register that measure time, error rate and success completion in a task. Result indicate that the office experiences the most friction during the registration and filing stages of the process. This is mainly due to slow,manual document verfication, limited automatic validation, and repetitive errors within the e-filing system. Streamling workflows, incorporating automated validation, and desighing real-time feedback loops that adhere to the principles of compliance by design noticeably decrease time spent in a process and improve conversion rates for compliance. This study proposes the establishment of a compliance funnel and a 30/60/90-day strategic intervention roadmap as a more tangible way to enhance performance of the digital tax service.